Frontiers in Synaptic Plasticity: Dendritic Spines, Circuitries and Behavior - Oliver von Bohlen und Halbach (Frontiers Research Topics, 2016)
The term "synaptic plasticity" is a broad concept, which is studied with a variety of experimental approaches. One focus is the impact of changes in synaptic, neuronal and glial morphology on brain circuitry and behavior. In this regard, unique animal models have been key to the study of affective and social behaviors and neurological and psychiatric diseases. However, there is a paucity of compilations directed toward the correlation of alterations in synaptic structure with various physiological and behavioral paradigms. This Frontiers Research Topic will, therefore, serve as an exciting forum for the exchange of novel hypotheses and data and an important resource and reference for investigators studying synaptic and brain plasticity, as well as those in related fields.